Perception of Space of Andrzej Stasiuk’s Beskid Stories - Mityk, Iwona (Respectus Philologicus, 2025)
Polish writer Andrzej Stasiuk is a representative of the generation born around 1960. The Low Beskids region serves as the backdrop for several collections of his stories, including Opowieści galicyjskie, Dukla and Zima. In this context, the role of the narrator, as conceived by Stasiuk, is of particular significance. This article explores how the narrator perceives the terrain. Philological analysis has shown that the author focuses on describing transformations that occurred in the area in the 1990s in ordinary people’s lives, but also on the regional nature. The presented backwoods are viewed in opposition to industrial centres, and the standstill in this area is in opposition to an active lifestyle in the external world, majestic mountains to human valleys, severe nature to civilisation, and the present time to the past. The narrator’s role is twofold: he reports on the protagonists’ actions while concurrently offering personal reflections. The author’s primary focus is on the concept of place and, more specifically, on the perception of place. The physical space is integral to the formation of nature and characters; however, the mental space is particularly salient insofar as it refers to the narrator’s mode of perceiving reality.